A report of the major farm practice in Robina Farms Cebu - Bareja, Mechelin A.; Remandaban, Eleanor T.; Lagman, Ner B. (Tacloban City Agricultural and Rural Development, University of the Philippines College Tacloban, 1981)
This study describes the observed operations management of large scale poultry farms, Robina Farms I (Commercial Layer Farm) and II (Breeder Farm) in Cebu.
Undergraduate thesis (Bachelor of Science in Animal Science)--University of the Philippines College Tacloban, Summer 1981.
Keywords: Robina Farms; Poultry -- Farm management and production; Poultry industry -- Cebu; Poultry breeding